Quando preferir um samba ao hino nacional é crime: integralismo, etnicidade e os crimes contra o estado e a ordem social (Espírito Santo 1934-1945) - Ackermann, Silvia Regina (2009)
This work focuses on the State of Espírito Santo in the 30 and 40 decades in the 20th century and aims to analyze the conflicts that took place in the meeting of two relevant events of this period: the repression to the Integralism and the consequences of the Second World War. It is important to stand out that the State of Espírito Santo, as well as other Brazilian States, had its history marked by European immigration in the 19th century. At that time the state received, mainly, Pomeranian/German and Italian immigrants. Part of these immigrants and descendants, in the decade of 30, acted in Brazilian Integralist Action (AIB), a right extreme party and influenced by European Nazi-fascism. Some conflicts that imbricated ethical issues and the acting of AIB, officially forbidden since the coup of the New State, became more visible and resulted in criminal proceedings. It was ascertained that AIB had strong presence in Espírito Santo, especially, in the regions of Pomeranian/German and Italian settlement. Also, it was verified that ethical conflicts did not seem to be so prominent as it was expected to. It seemed that the major conflicts were marked by a nationalistic feeling and confrontations that still had AIB as an explanation. It can also be suggested that differentiated cultural practices of the immigrants and descendants were not understood as so dangerous by the government since they were followed of economic and politic status, for instance, case of the South of Brazil. Originated criminal proceedings in the State of Espírito Santo, which were presented at the court of National Security (TSN), were used as privileged sources. Some paper was analyzed such as: documents and photographs apprehended by the Espírito Santo police from AIB nucleus, official letters from the Education and Justice department, newspaper and magazines, besides interviews with inhabitants of Domingos Martins city (ES). The historical event reported starts with AIB National Congress in Vitória (1934) and it closes up with the Second World War end (1945). Key words: Brazilian Integralist Action. Second World War. Immigrants. Criminal Proceedings. National Security Court.